Thank you for the opportunity to help you with your question!

you will first have a function, y=f(x)+c. you need to transform so that you can have another function. you move a function up by adding a constant to y-value

we move a function right or left by adding a constant to x-value

you can compress to y by multiplying. the whole function by a constant

and you can also compress it to x direction by multiplying x when it appears by a constant.

y = f(x) + C

C > 0 moves it up

C < 0 moves it down

y = f(x + C)

C > 0 moves it left

C < 0 moves it right

y = C·f(x)

C > 1 stretches it in the y-direction

0 < C < 1 compresses it

y = f(Cx)

C > 1 compresses it in the x-direction

0 < C < 1 stretches it

y = -f(x)

Reflects it about x-axis

y = f(-x)

Reflects it about y-axis

Please let me know if you need any clarification. I'm always happy to answer your questions.